Perfusion pressure as a determinant of respiratory function outcomes in unilateral biportal lumbar endoscopic procedures - Zhang, Liang; Zheng, Han; Fu, Yan; Li, Wenbo; Lang, Jianlong; Wang, Yi; Ren, Weibin (Frontiers in Pharmacology, 2025)
IntroductionUBE is used to treat most lumbar spine diseases, and it must rely on continuous infusion of saline to maintain a clear field of vision during the operation to ensure the smooth progress of the operation. Among many complications, the incidence of dural tear is the highest. Whether UBE can damage the dura and the effect of intraoperative perfusion pressure changes on respiratory function under different conditions are not clear.MethodsIn the present experiment, Wistar rats were implanted with diaphragmatic electrodes and divided into two groups (dura mater with rupture group and dura mater without rupture group). In the experiment, the perfusion pressure was continuously increased, and the water pressure was 6KPa, 10KPa and 14Kpa for 2 min, respectively. The changes of respiratory movement were observed and analyzed. The preoperative and postoperative MRI scan results were compared. Pathological staining was used to observe the spinal cord injury.ResultsFinally, we found that high perfusion pressure impaired respiratory function in rats with dural rupture, mainly manifested as decreased respiratory rate, but had no significant effect on respiratory function in rats with intact dura mater. HE staining and toluidine blue staining showed more nishi in the cauda equina nerve of the rats in the dural rupture group. Immunofluorescence results showed that the degree of cauda equina nerve injury in the dural rupture group was more severe than that in the dural rupture group.DiscussionThis study reveals the effects of perfusion pressure and dural injury on respiratory function in UBE, and avoiding dural sac rupture is an effective means to prevent and treat complications of UBE, which will provide a new perspective on UBE.